Assessing the effect of per operative intravenous injection of tranexamic acid in patients undergoing arthroscopic anterior cruciate ligament reconstruction - Pande, Ashish; Bhaskarwar, Ajit P. (International Journal of Research in Orthopaedics, 2019)
Background: Anterior cruciate ligament (ACL) tear is a common injury sustained during contact games hampering performance of the sportsmen and thus requires promt management. Arthroscopic ACL reconstruction is commonly associated with postoperative knee effusion which affects the functional recovery. Various treatment modalities are available for managing effusion after ACL reconstruction, which are associated with various grades of success and side effects. Methods: This prospective interventional study was carried out at tertiary care Orthopaedic centre. It involved 48 Young male athletes with ACL tear managed subsequently by arthroscopic ACL reconstruction. Subjects were divided into Injection group and non injection group by randomization and blinding was ensured. Postoperative rehabilitation, prophylactic antibiotic and chemoprophylaxis for DVT was kept standardised for all patients. Patients were assessed for pain at operative site by visual analogue scale, effusion of knee by classification of Coupens and Yates and Lysholm knee scoring at 2nd, 6th and 12th week postoperatively. Results: During follow ups it was found that Injection group was having significant less incidence of effusion as compared with Non injection group; which also has reflected in functional recovery. Conclusions: It can be concluded that use of inj tranexamic acid preoperative dose in case of patients undergoing ACL reconstruction is efficient to reduce the knee effusion.